ANALISIS YURIDIS PEMBERIAN HAK GUNA USAHA TERHADAP PERUSAHAAN ASING DALAM BENTUK JOINT VENTURE SETELAH UNDANG UNDANG NOMOR 25 TAHUN 2007 TENTANG PENANAMAN MODAL - RUBEN SIANIPAR (PREMISE LAW JURNAL, 2015)
The result of the research showed that the procedure in giving Leasehold on the request by applicants to obtain Leasehold to Head of the National Land Board is regulated in the Regulation of Head of the National Land Board, with a copy to Regional Chief Executive. Before requesting Leasehold, a foreign investor is required to be an Indonesian legal entity or a Corporation in which it is required to perform joint venture with Domestic Investment according to the prevailing rules. A foreign company as an applicant is required to request in written form to Head of the Land Office by attaching his personal data and the Request for Leasehold. Head of the National Land Board then processes the issuance of the Decree of Leasehold and gives it to the applicant; after that, the applicant is required to immediately take a responsibility by paying an amount of money for State’s revenues and land and building acquisition fee. Keywords: Leasehold, Capital Investment, Joint Venture, Foreign Company